Overexpression of FcεRI on Bone Marrow Mast Cells, but Not MRGPRX2, in Clonal Mast Cell Disorders With Wasp Venom Anaphylaxis - Elst, Jessy; De Puysseleyr, Leander P.; Ebo, Didier G.; Faber, Margaretha A.; Van Gasse, Athina L.; van der Poorten, Marie-Line M.; Decuyper, Ine I.; Bridts, Chris H.; Mertens, Christel; Van Houdt, Michel; Hagendorens, Margo M.; De Clerck, Luc S.; et al. (Frontiers in Immunology, 2022)
Background: Uncertainties remain about the molecular mechanisms governing clonal mast cell disorders (CMCD) and anaphylaxis. Objective: This study aims at comparing the burden, phenotype and behavior of mast cells (MCs) and basophils in patients with CMCD with wasp venom anaphylaxis (CMCD/WVA+), CMCD patients without anaphylaxis (CMCD/ANA-), patients with an elevated baseline serum tryptase (EBST), patients with wasp venom anaphylaxis without CMCD (WVA+) and patients with a non-mast cell haematological pathology (NMHP). Methods: This study included 20 patients with CMCD/WVA+, 24 with CMCD/ANA-, 19 with WVA+, 6 with EBST and 5 with NMHP. We immunophenotyped MCs and basophils and compared baseline serum tryptase (bST) and both total and venom specific IgE in the different groups. For basophil studies, 13 healthy controls were also included. Results: Higher levels of bST were found in CMCD patients with wasp venom anaphylaxis, CMCD patients without anaphylaxis and EBST patients. Total IgE levels were highest in patients with wasp venom anaphylaxis with and without CMCD. Bone marrow MCs of patients with CMCD showed lower CD117 expression and higher expression of CD45, CD203c, CD63, CD300a and FcεRI. Within the CMCD population, patients with wasp venom anaphylaxis showed a higher expression of FcɛRI as compared to patients without anaphylaxis. Expression of MRGPRX2 on MCs did not differ between the study populations. Basophils are phenotypically and functionally comparable between the different patient populations. Conclusion: Patients with CMCD show an elevated burden of aberrant activated MCs with a significantly overexpression of FcεRI in patients with a wasp venom anaphylaxis.